Investigation of student's satisfaction from the laptop desks using satisfaction questionnaire - M. Jafarvand; N. Marandi; S. Varmazyar; E. Mohammadi (The Journal of Qazvin University of Medical Sciences, 2018)
Background: User satisfaction from a device is an especially term in the design world that covers broad concept of the design content. Objective: The aim of the present study was to design satisfaction questionnaire and survey of satisfaction of student's from the laptop desks. Methods: This analytical - descriptive study has conducted for survey student's satisfaction from the laptop desks in the male dormitories of Qazvin University of Medical Sciences in 2017. Fifty students (17 boys and 33 girls) were recruited by simple stratified random sampling. Based on scientific literature and point of view faculty member and student, 43 items of questionnaire were drafted and reliability and validity were evaluated and only 23 question confirmed. Data analyzed using Pearson correlation and Cronbach's alpha. The percentage of students' satisfaction was determined using cut-off point of questionnaire in receiver operating characteristic (ROC) curve. Findings: The results of Cronbach's alpha and correlation of questionnaire obtained 0.95 and 0.83 respectively. According to the ROC curve, cut-point of satisfaction questionnaire of the students from laptop desks obtained 64.5. Then, the percent of student satisfaction (boys and girls) from desk 1 and 2 were 47.1%, 66.7% and 11.8%, 42.4% respectively. Conclusion: One-third of students from desks were dissatisfied. So, the use of opinion ergonomics specialists and particularly users when designing is necessary for increase user's satisfaction from design of laptop desks.